The Influence of Systemic Inflammation Response Index on Survival Outcomes of Limited-Stage Small-Cell Lung Cancer Patients Treated with Concurrent Chemoradiotherapy. (17th December 2020) - Kucuk, Ahmet; Ozkan, Emine Elif; Eskici Oztep, Sukran; Mertsoylu, Huseyin; Pehlivan, Berrin; Selek, Ugur; Topkan, Erkan
Abstract : Background . Recent studies have indicated that the systemic inflammation response index (SIRI) can efficiently predict survival outcomes in various tumor types. Thusly, in absence of comparable investigations in limited-stage small-cell lung cancers (LS-SCLCs), we aimed to retrospectively evaluate the prognostic utility of SIRI in LS-SCLC patients treated with concurrent chemoradiotherapy (CRT). Patients and Methods . Present multi-institutional retrospective analysis incorporated LS-SCLC patients treated with CRT at three academic radiation oncology centers between January 2007 and December 2018. The SIRI was calculated by using the peripheral blood neutrophil (N), monocyte (M), and lymphocyte (L) counts acquired in the last ≤7 days before the commencement of the CRT: SIRI = N × M/L. Accessibility of pretreatment SIRI cutoff that may stratify the study population into two gatherings with distinctive overall survival (OS) results was evaluated by utilizing the receiver operating characteristic (ROC) curve analysis. Primary objective was the association between the SIRI values and the OS results. Results . Search for the availability of an ideal SIRI cutoff that may stratify the entire patients' population into two particular groups with distinctive OS outcomes identified the 1.93 value (area under the curve (AUC): 72.9%; sensitivity: 74.6%; specificity: 70.1%): Group 1: SIRI <1.93 ( N  = 71) and Group 2: SIRI ≥1.93 ( N  = 110), respectively. At a median follow-up of 17.9 (95% CI: 13.2–22.6) months, 47 (26.0%) patients were still alive (47.9% for SIRI <1.93 versus 18.3% for SIRI ≥1.93; p < 0.001 ). Kaplan–Meier comparisons between the two SIRI groups showed that the SIRI <1.93 cohort had significantly longer median OS (40.5 versus 14.2 months; p < 0.001 ) than the SIRI ≥1.93 cohort. Similarly, the 3- (54% versus 12.6%) and 5-year (33% versus 9.9%) OS rates were also numerically superior in the SIRI <1.93 cohort. Results of the multivariate analyses uncovered that the prognostic significance of the SIRI on OS outcomes was independent of the other confounding variables. Conclusions . The results of this retrospective multi-institutional cohort analysis suggested that a pre-CRT SIRI was a strong and independent prognostic biomarker that reliably stratified LS-SCLC patients into two cohorts with significantly different OS outcomes.